Probiotic Fermentation of Rice Bran with Six Genetically Diverse Strains Effects Nutrient and Phytochemical Composition; a Non-Targeted Metabolomics Approach. (29th May 2020) - Demissie, Yohannes; Humblot, Christèle; Baxter, Bridget; Nealon, Nora Jean; Ryan, Elizabeth
Abstract: Objectives: This study examined the contributions of native gut probiotic bacteria in production of rice bran microbial metabolites with bioactivity and nutritional importance. The study hypothesize that bacteria and yeast probiotics utilize distinct genes for bidirectional influence on bacterial cross feeding and host bioavailability of rice bran vitamins, while decreasing undesirable molecules. Methods: A one/two step fermentation protocol was applied to rice bran (RBT-300) with the following strains Lactobacillus fermentum ATCC 23271, L. paracasei ATCC 21052_R1, L. rhamnosus GG, Escherichia coli Nissle 1917, and Bifidobacterium longum ATCC 55813 before and after incubation with yeast probiotic Saccharomyces boulardii . Metabolomic analysis was performed following 80% methanol-water under vigorous shaking (2 min) followed by centrifugation to remove proteins. Extracts were applied to reverse phase (RP)/UPLC-MS/MS methods with positive and negative ion mode electrospray ionization. Results: The rice bran metabolite profile in the presence of fermentation yielded 613 unique biochemical compounds of known identity across 8 major chemical classes. The bacterial strains used alone or after yeast fermentation modified about 70% of the metabolome and 60% total vitamins. For instance, vitamin B6 changed by strain L. rhamnosus GG (increased fivefold) when compared to rice bran, and supports the role for bacterial gene/enzyme in increased production. Findings were supported by decreased metabolite precursor. Phytate degradation persisted across this cocktail of probiotics that can further enhance nutrient bioavailability. Conclusions: The metabolomics approach for fermented rice bran analysis allows for information across other diverse pathways including protein, lipids, prebiotics and phenolics. The inclusion of the probiotics genetic potential and diversity are criteria for rice bran fermentation that merit continued attention for its functional impact on gut health and immunity. Funding Sources: National Institutes of Health-National Cancer Institute (3R01CA201112-04S1).